2019
DOI: 10.3390/molecules24183234
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Disubstituted Pyrimidines as Selective 5-HT2C Agonists

Abstract: Here, we describe the synthesis of disubstituted pyrimidine derivatives and their biological evaluation as selective 5-HT2C agonists. To improve selectivity for 5-HT2C over other subtypes, we synthesized two series of disubstituted pyrimidines with fluorophenylalkoxy groups at either the 5-position or 4-position and varying cyclic amines at the 2-position. The in vitro cell-based assay and binding assay identified compounds 10a and 10f as potent 5-HT2C agonists. Further studies on selectivity to 5-HT subtypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this way, Sel showed a strong affinity with 5-HT 2A and 5-HT 2C receptors in the molecular docking studies. The interactions between Sel and 5-HT 2A/C amino acid residues are similar to those of other ligands of 5-HT 2A/C receptors. ,,,,, However, further studies are needed to elucidate if SeI binds 5-HT 2A and 5-HT 2C receptors and how these possible interactions affect the 5-HT 2A/C receptors.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this way, Sel showed a strong affinity with 5-HT 2A and 5-HT 2C receptors in the molecular docking studies. The interactions between Sel and 5-HT 2A/C amino acid residues are similar to those of other ligands of 5-HT 2A/C receptors. ,,,,, However, further studies are needed to elucidate if SeI binds 5-HT 2A and 5-HT 2C receptors and how these possible interactions affect the 5-HT 2A/C receptors.…”
Section: Resultsmentioning
confidence: 92%
“…In the 5-HT 2C receptor docking study, Sel made pi–alkyl hydrophobic interactions with Val215, Val135, Phe328, Phe223, Trp324, and hydrogen bonds with Ala222 (Figure B). The hydrophobic contact with Val135, Phe328, Trp324, and Val215 also has been described and could be relevant to the action of 5-HT 2C ligands. , The residues Val135 and Phe328 of the 5-HT 2C receptor have been related to the binding of 5-HT 2C antagonists. However, a comparison among 5-HT 2C agonists and antagonist binding modes demonstrated that they share the same pocket with a different orientation …”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] Lactic acid bacteria are often used as microbial starter for rice fermented products, and a variety of organic acids are produced during the fermentation process, resulting in acidification, which can also mask the unpleasant smell of the product itself. [ 12,13 ] Lactobacillus spp. is the dominant bacterial genus for fermenting sticky rice products.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many efforts have been made to identify 5-HT 2C R agonists and positive allosteric modulators. 5-HT 2C R agonists generally possess a high structural similarity to the endogenous ligand serotonin (5-HT), as depicted in Figure and Figure S1, consisting of a basic amine, an aromatic ring, and a linker connecting them. Only lorcaserin has once been approved by the FDA as a selective 5-HT 2C R agonist for the treatment of obesity; unfortunately, it was later withdrawn from the market due to concerns regarding potential increased risk of cancer associated with long-term use .…”
mentioning
confidence: 99%